Keratin hydrolysate improves the production of commercially valuable metabolites - da Silva, Ronivaldo Rodrigues [UNESP] (Springer Nature, 2024)
In the integration of the circular economy, keratin hydrolysis is essential for preventing keratin accumulation in the environment and offers opportunities for utilising the resultant protein hydrolysate. Keratin hydrolysate can serve as an alternative nitrogen source for microbial cultures, and thus promote cost-effective production of commercially valuable metabolites such as biofuels, vitamins, organic acids, pigments, and polysaccharides. Considering the amount of keratin waste generated annually, particularly chicken feathers, exploring alternative approaches for utilising keratin hydrolysate could stimulate further research.
Keywords: Bacteria; Biofuel; Feather; Fungi; Peptides; Protein hydrolysate